Hubungan Pengetahuan Potensi Peningkatan Tekanan Darah Dengan Pola Makan pada Lansia - Risnawati Risnawati; Astuti Suardi; Ulvy Pratiwy D; Haedir Haedir; Natalia Datu (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Hypertension is a non-communicable disease and is quite common in Indonesia and throughout the world. This condition is characterized by a continuous increase in blood pressure. Several studies have shown that the higher a person's blood pressure, the greater the risk of experiencing heart disease, kidney failure, and stroke. The purpose of this study was to determine the relationship between knowledge of the potential for increased blood pressure and dietary patterns in the elderly. This study used Descriptive Analytical research with a Cross-Sectional approach. The sample in this study was 38 elderly people aged 60-80 years using Purposive Sampling techniques. Data analysis with univariate and bivariate analysis using Chi Square. The results of statistical analysis showed that there was a relationship between knowledge of the potential for increased blood pressure and dietary patterns in the elderly (p = 0.001). The conclusion of this study is that there is a relationship between knowledge of the potential for increased blood pressure and dietary patterns in the elderly in Bilante Village, Larompong District, Luwu Regency. Healthcare professionals should be more active in providing IEC (Communication, Information, and Education) to the elderly regarding the importance of dietary management in preventing high blood pressure.